Studi Penggunaan LPG Dari Aktivitas Rumah Tangga Di Wilayah Pengembangan IV Kota Pekanbaru - Ribka Yunila; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The purpose of this study was to find out the use of LPG household fuels in WP IV Pekanbaru City.Random sampling method. Total sample is 268 families. This study uses descriptive analysis that contains secondary data, study of literature, and primary data. About 85% of respondents only use LPG as domestic fuel,12% use LPG fuel and other fuels, and 3% use other LPG.Keywords: Use of household LPG, LPG, and Household